Analisis Faktor yang Mempengaruhi Keputusan Pembelian Konsumen terhadap Pembersih Wajah Ovale - Wijayanti, Ratna (Jurnal Aplikasi Manajemen, 2008)
In accordance with the technology development, the beauty variation and mode in Indonesia also develop, signed by the development of cosmetics product with various types and complete colors choice. The cosmetics companies are expected to be proactive on facing the technological changes and the strict competition by giving excessive values to the products, so that each of the product will bring the different impression. The consumers always evaluate the products which are considered fulfill their needs and look for the information which are relevant with their needs before making decision to buy the products. This research aim at knowing the factors that influence the decision of buying the face cleaner namely Ovale and knowing the significance of those factors. This research uses factor analysis as the instrument to identify the significance level of the factors which influence the decision making to buy the Ovale face cleaner. The result of this research shows there are three main factors which influence the consumers to buy Ovale face cleaner i.e., product, price, and promotion factors. The result of hypothetical test shows that product factors is the most dominant factor that affect the consumer to buy Ovale face cleaner.